A Concept of Regionalism-Contemporary Architecture in Rest Area Design (JLSS Purworejo, Central Java) - Cinthyaningtyas Meytasari; Ray Bagas Andriyanto (Program Studi Arsitektur Fakultas Teknik Universitas Mataram, 2021)
Humans are social creatures who often travel, to get out of their environment. Differences in the people who occupy an area will affect the resulting culture, both intangible and tangible. Related to this, a trip often takes a long route that requires a temporary resting place (called a rest area), which is placed at the tired points of the travelers. The rest area is one of the 'gateways' when travelers enter a certain area, so the rest area must be able to represent the local culture because the rest area is used as a manifestation of regional identity. The concept of Regionalism-Contemporary Architecture is considered appropriate because through this concept the characteristics of the local area will be explored to be applied in the embodiment of a design, so as to represent the identity of the region, without leaving a vision of the future (modern). This concept will be applied in planning the rest area on the Southern Cross Road (JJLS) in the Purworejo area, Central Java. Keywords: rest area; regional characteristics; regionalism-contemporary architecture; JJLS Purworejo